Dissonances in communication with sexual health consumers in an inner‐Sydney sexual health clinic in relation to health literacy: A mixed‐methods study. (26th October 2020) - McCormack, Heather; Nathan, Sally; Varma, Rick; Haire, Bridget
Abstract: Issues addressed: This study examined the navigation of health care interactions by health consumers attending Sydney Sexual Health Centre (SSHC), an inner‐city sexual health clinic in Sydney, Australia. We aimed to assess the accessibility and appropriateness of communications between SSHC and patients in the context of health literacy. Methods: We conducted 20 semi‐structured interviews with health consumers, assessed health literacy using the Short Health Literacy Assessment for English‐Speaking Adults (SAHL‐E) and conducted a focus group with clinical staff. Results: We identified dissonances around assumed knowledge in communications between health professionals and health consumers, which were most apparent when lack of knowledge about sexual health, HIV and pre‐exposure prophylaxis (PrEP) intersected with poor English fluency. So what?: This study suggests that existing models of access for HIV treatment and PrEP in Australia have been developed for high health literacy and may not support consumers who experience communication barriers due to low health literacy. The Australian Commission on Safety and Quality in Health Care recommends addressing health literacy systemically, including embedding assessment of health literacy into organisational systems and policies. We recommend developing tools to assess knowledge levels of consumers accessing sexual health services and incorporating health literacy into clinician training on working with patients from non‐English–speaking backgrounds.